Effects of adenoviral-mediated gene transduction of NK4 on proliferation, movement, and invasion of human colonic LS174T cancer cells in vitro - Jie, Jian-Zheng (Baishideng Publishing Group Co., Limited, 2006)
AIM: To investigate the inhibitory effects of a recombinant adenovirus vector that expresses NK4, a truncated form of human hepatocyte growth factor (HGF), on human colonic adenocarcinoma cells in vitro to establish a basis for future NK4 gene cancer therapy. METHODS: Cells from the LS174T human colonic adenocarcinoma cell line were infected with recombinant adenovirus rvAdCMV/NK4 and the effects of the manipulation on tumor cell proliferation, scatter, migration, and basement membrane invasion were assessed. Cells infected with a recombinant adenovirus vector (Ad-LacZ) expressing β-galactosidase served as the controls. RESULTS: We found that rvAdCMV/NK4 expression attenuated HGF-induced tumor cell scatter, migration, and basement membrane invasion (P < 0.05), but did not inhibit tumor cell proliferation. CONCLUSION: HGF-induced LS174T tumor cell scatter, migration, and invasion can be antagonized by the recombinant NK4-expressing adenovirus.